Relatives and Non-Relatives in the Narrative of Decentralized Political Culture in Indonesia - Pangeran P.P.A. Nasution (Jurnal Transparansi Publik (JTP), 2025)
The decentralization system, as a reality of democratic implementation in various regions in Indonesia, with direct elections for regional heads, is marked by the rise of kinship politics. As a strategy to secure power, kinship politics involves involving family and relatives in holding certain political positions, both formally and informally. This article aims to outline the aspects supporting the escalation of kinship politics in Indonesia. The research method used to organize and present the data in this paper is a literature review, examining manuscripts and documents related to decentralization, regional head elections, kinship politics, political culture, and leadership. The study found that the strengthening of kinship politics in the era of decentralization is inseparable from the existence of a political culture in Indonesian society that is oriented towards the role of opinion leaders or indigenous figure leadership. Local leaders gain a clear electoral advantage due to their popularity, substantial financial resources, and ability to mobilize the masses. Kinship politics also has the potential to reinforce nepotism, patron-client relations, patrimonialism, and recruitment patterns based on kinship representation. Kinship politics has the potential to become a latent threat to the development of democracy, especially amidst the trend of decentralized politics in Indonesia.